The Effect of Product Quality and Price on Purchase Intention with Perceived Value As Moderating Variables For Seafood Tomato Udon Products At Marugame Udon: Pengaruh Kualitas Produk dan Harga terhadap Niat Pembelian dengan Persepsi Nilai sebagai Variabel Moderasi untuk Produk Seafood Tomato Udon di Marugame Udon - Parbowo, Teguh; Wirakartakusumah, Aman (Sekolah Tinggi Manajemen IPMI, 2025)
Marugame Udon is a restaurant that serves Japanese fried udon and tempura dishes in Indonesia. This research aims to analyze the role of product quality and price with perceived value as a moderating variable on purchase intention toward seafood tomato udon product at marugame udon restaurant in Jakarta. The research method used in this study is a quantitative method using multivariate data analysis model, including Partial Least Square Structural Equation Modelling (SEMPLS), which samples from 150 respondents of Marugame Udon customers in Greater Jakarta. This research uses questionnaires with likert scale. Results of this research show that Product Quality has a positive effect and significant on Purchase Intention, Perceived Value has a positive effect and not significant on Purchase Intention, Perceived Value has moderated a positive effect on Price and Purchase Intention, Price has a positive effect and significant on Purchase Intention, and Product Quality has a positive effect and significant on Price. For further research, academics can explore these topics within other food companies. Another recommendation for future studies is to employ different sampling methods, such as stratified random sampling or systematic random sampling, to achieve a more diverse respondent pool. Increasing the number of research samples can lead to more precise findings and expanding the sampling locations can help capture a broader range of customer characteristics. For management, it is necessary to consider the time for launching food products in accordance with the targeted segment. For example, during a period when the number of customers is declining or it's a low season, management is expected to introduce products that are likely to be accepted by all market segments,